Hydrologic characterization of upper Permian-Cenozoic sedimentary strata of Larimer County: prospective aquifer storage and recovery targets - Adam, Adam, author; Sutton, Sally, advisor; Sanford, William, committee member; Sale, Thomas, committee member (Colorado State University. Libraries, 2017)
Providing adequate water storage is an on-going problem along the northern Colorado Front Range. This study compiles existing hydrogeological data from water wells to identify potential ASR sites in eastern Larimer County, Colorado. These water well data are used to evaluate both geographic localities and individual lithologic units. All stratigraphic units younger than the Pennsylvanian-Permian Fountain Formation and reported to host water wells in eastern Larimer County are considered here. A total of 1094 AquaMap water well reports have been mined for data, including depth, pumping level, static water level, lithology, location, date drilled, and yield. Additionally, specific capacity has been calculated for each well. The data points were plotted using ArcGIS and geological maps from US Geological Survey as base maps. The main parameters considered are water well yields and specific capacities. Yield is an indication of the ability of an aquifer to permit movement of water, but the yield data available may not reflect the maximum ability of a well to produce or store water. This is because water is pumped out according to the usage or purpose of the well, with irrigation and livestock wells typically yielding more than household wells. In some locations the aquifers considered can likely produce more than indicated by reported yields. Based on both hydrogeological properties and widespread occurrence in the study area the Pierre Shale Formation, the Lytle Formation, and the Ingleside Formation appear to show the greatest promise as ASR targets. Additional units that could be worth further consideration include the Jelm and Lykins Formations. Based solely on hydrogeological data, the White River, Laramie, and Fox Hills Formations would be the strongest candidates for ASR, but are geographically limited to the far northeast corner of the county. In addition, well data from unconsolidated alluvial deposits suggest strong potential for ASR, especially near the eastern edge of the County, but the combination of very high permeability and surface exposure would make ASR in these deposits challenging because of difficulty maintaining control of stored water. Based on well data, there are some specific localities that may merit further consideration for ASR, including the vicinity of Laporte, where several stratigraphic units host wells with high yields and high specific capacities. Similarly, there are wells in several stratigraphic units, including the Pierre Shale Formation, CarlileGraneros-Mowry Shales, Owl Canyon Formation, Lyons Formation, and Lytle Formation, in an area to the west of Loveland that show promise for ASR. Additionally, the Pierre Shale Formation hosts several clusters of wells indicating strong potential for ASR; the best developed of these clusters are in the northern third of the Larimer County, specifically northwest of Wellington.